PENGARUH PENAMBAHAN TEPUNG KUNYIT DAN BETAIN PADA RANSUM TERHADAP BERAT KARKAS, TEBAL LEMAK PUNGGUNG DAN LOIN EYE AREA BABI FINISHER (Effect of Dietary Turmeric Flour and Betain Addition on Carcass Weight, Backfat Thickness and Loin Eye Area of Finisher Pig) - Jimmi RH Sinaga; Sauland Sinaga; Denny Rusmana (Jurnal Ilmu dan Teknologi Peternakan, 2020)
Antibiotic Growth Promoter (AGP) synthetic as a feed additive can stimulate growth, prevent some health problems, and improve feed efficiency. However, its journey has raised concerns due to adverse effects such as residues and microbial resistance. The use of turmeric flour and betaine as feed additives is expected to substitute the use of AGP Synthetic in improving the performance of pig carcasses and the safety of consumption. This study was aimed to examine the effect of the addition of turmeric flour and different doses of betaine in the ration on the performance of finisher period pigs. The study was conducted experimentally using a completely randomized design with four treatments and five replications. The objects of the study were 20 male and female finisher Landrace pigs with a finisher period with initial body weights of 55-66 kg/head. The study rations used were R0: basal ration, R1: R0 + 0.4% turmeric flour + 0.1% betaine, R2: R0 + 0.4% turmeric flour + 0.15% betaine and R3: R0 + 0.4% turmeric flour + 0.2% betaine. The parameters measured were carcass weight, backfat thickness, and loin eye area. The addition of turmeric flour treatment did not have any significant effects on carcass weight and thickness of the back fat of the pig. The addition of 0.4% turmeric flour and 0.15% betaine in the ration was the best treatment and resulted in a different effect on the loin eye area compared to that of R0, while treatment R1 and R3 had a similar effect on it. The result of the addition of 0.4% turmeric flour and 0.15% betaine resulted in the loin eye area of the finisher pig of 53.4 cm2